1999
DOI: 10.1172/jci5346
|View full text |Cite
|
Sign up to set email alerts
|

DMPK dosage alterations result in atrioventricular conduction abnormalities in a mouse myotonic dystrophy model

Abstract: The disorders of skeletal muscle and cardiac function observed in myotonic dystrophy (DM) occur as a consequence of a CTG repeat expansion (1, 2) located in the 3′ untranslated region of a protein kinase, myotonic dystrophy protein kinase (DMPK; 3, 4), on chromosome 19q13.3. The molecular mechanisms by which expanded CTG sequences produce DM pathophysiology remain unresolved, though three models prevail. First, partial loss of DMPK resulting as a consequence of nuclear retention of the mutant DMPK mRNA may con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 35 publications
(38 reference statements)
7
108
1
1
Order By: Relevance
“…It has been shown that CTG repeats reduce expression of myotonin protein kinase in cis (4), causing abnormalities in cardiac muscle (5). CTG repeats also affect transcription of genes adjacent to myotonin protein kinase (6), leading to the development of cataracts (7,8).…”
Section: Dm1mentioning
confidence: 99%
“…It has been shown that CTG repeats reduce expression of myotonin protein kinase in cis (4), causing abnormalities in cardiac muscle (5). CTG repeats also affect transcription of genes adjacent to myotonin protein kinase (6), leading to the development of cataracts (7,8).…”
Section: Dm1mentioning
confidence: 99%
“…30,33 Mice were studied 1 day after Holter recording. Briefly, animals underwent endotracheal intubation and were ventilated.…”
Section: Invasive Electrophysiological Study Protocolmentioning
confidence: 99%
“…Myoblast cell culture models 5,6 and subsequently a transgenic mouse model 7 have provided strong evidence for the involvement of RNA containing expanded CUG repeat tracts in aspects of DM1 skeletal muscle pathology. However, there is no clear model of RNA toxicity in the heart, and instead it has been suggested that DM1 cardiac pathology may be due to misexpression of DMPK 8,9 .…”
mentioning
confidence: 99%